A preliminary investigation of the transition from green building to green community: Insights from LEED ND - Wu, Peng; Song, Yongze; Hu, Xin; Wang, Xiangyu (M D P I AG, 2018)
© 2018 by the authors. The Leadership in Energy and Environmental Design for Neighborhood Development (LEED ND) rating system has been considered one of the major tools to assess the performance of green communities. However, few studies have been conducted on how the traditional focus on green building can be effectively transitioned to green communities. In order to facilitate the transition process, this paper reviews and analyzes the credits obtained from LEED ND 2009 certified plans. A total of 55 projects were identified from the LEED project directory of the U.S. Green Building Council. The performance of these neighborhood development projects, including project landscape, percentage of achievement and predictors of LEED ND rating, was analyzed. The performance was then compared with the performance of green buildings certified under LEED New Construction (LEED NC). The results indicate that there is an unbalanced allocation of credits to economic, social and environmental sustainability in the LEED ND rating. In addition, green infrastructure and building credits, such as wastewater management, on-site renewable energy and solar orientation, have extremely low percentage of achievement, indicating that these credits should be redesigned. The results provide useful insights for developers to prepare for LEED ND certification and for regulatory bodies to improve the performance of the current LEED ND rating system.